Neuroprotective Action and Free Radical Scavenging Activity of Guttiferone-A, a Naturally Occurring Prenylated Benzophenone - Nuñez-Figueredo, Y.; García-Pupo, L.; Ramírez-Sánchez, J.; Alcántara-Isaac, Y.; Cuesta-Rubio, O.; Hernández, R. D.; Naal, Z.; Curti, C.; Pardo-Andreu, G. L. (Arzneimittelforschung, 2012)
Reactive oxygen species (ROS) are important mediators in a number of neurodegenerative diseases and molecules capable of scavenging ROS may be a feasible strategy for protecting neuronal cells. We previously demonstrated a powerful iron-chelating action of Guttiferone-A (GA), a naturally occurring polyphenol, on oxidative stress injuries initiated by iron overload. Here we addressed the neuroprotective potential of GA in hydrogen peroxide and glutamate-induced injury on rat’s primary culture of cortical neurons and PC12 cells, respectively, and antioxidant properties concerning scavenging and anti-lipoperoxidative activities in cell-free models. The decrease in cell viability induced by each of the toxins, assessed by [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide] (MTT) assay, was significantly attenuated by GA. In addition, GA was found to be a potent antioxidant, as shown by (i) inhibition of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical reduction (EC50=20.0 μM), (ii) prevention against chemically or electrochemically generated superoxide radicals, (iii) inhibition of spontaneous brain lipid peroxidation and (iv) interference with the Fenton reaction. These results indicate that GA exerts neuroprotective effects against H2O2 or glutamate toxicity and its antioxidant activity, demonstrated in vitro, could be at least partly involved. They also suggest a promising potential for GA as a therapeutic agent against neurodegenerative diseases involving ROS and oxidative damage.
Keywords: PC12 cells; rat cortical neurons; glutamate; hydrogen peroxide; neuroprotective drug; Guttiferone-A